Pengaruh Employee Engagement, Worklife Balance, Dan Budaya Organisasi Terhadap Kinerja Karyawan (Studi Pada PT. Sumber Alfaria Trijaya Tbk) - Isma Latifah; Ibnu Haris Nasution (Prisani Cendekia, 2023)
Human resources are an important corporate asset that must be developed, because human resources become active planners and actors in every organizational activity in achieving goals. As an asset to the success of an organization, it is necessary to have an engagement between human resources and the company. One of the factors from the work environment that affects the work environment that affects employee engagement in carrying out daily work is organizational culture. This study aims to determine the effect of Employee Engagement, Worklife Balance and Organizational Culture on Employee Performance at PT Sumber Alfaria Trijaya Tbk. The population and sample in this study were all employees at PT Sumber Alfaria Trijaya Tbk, totaling 60 people. Data collection tool using a questionnaire with the Likert scale method. The research was processed and tested using the Smart PLS 4.0 application. This study aims to determine directly or indirectly the influence of employee engagement, work-life balance and organizational culture on employee performance at PT Sumber Alfaria Trijaya Tbk. The results showed that Worklife Balance and Organizational Culture have a positive effect on Employee Performance, while Employee Engagement has a negative effect on Employee Performance